Alaya a Kapampangan culinary heritage museum - Manucom, Raissa Stefannie N.; Varona, Maria Faith Y. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Angeles City, due to its proximity to Clark, has enjoyed continuous growth in the past century. However, with the air base base also came the growth of its infamous red light district that survived even after most military presence had left Clark. To combat this, the local government has turned to other forms of tourism not only for the promotion of a better image of the city, but also for the economic benefit of its citizens. With this in mind, the idea for Alaya, a Culinary Heritage Museum, was born. The development first seeks to establish Angeles as a culinary destination in the region being the economic center of Pampanga which has often been dubbed as the "culinary capital of the Philippines". Secondly, the development seeks to highlight the relationship between food and tradition. Lastly, it seeks to connect the experience of food to the landscape, not only from its sourcing, but also to the act of dining. These three agenda were followed to come up with a new building type that can house new culinary experiences in the form of the interactive museum galleries, dining establishments, and park places.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Museums; Museums -- Pampanga -- Philippines